Childhood immunisation: what is the future? - Pollard, A (2007)
Improved immunisation programmes and the development of new vaccines provide unprecedented opportunities to improve and sustain the health of our children. There are major challenges ahead in communicating the benefits of immunisation to all populations and in delivering vaccines to those in greatest need. In this review on immunisation, I have asked international opinion leaders to comment on the present and the future of immunisation to provide signposts for the narrative.